2015
DOI: 10.1017/s1368980015001366
|View full text |Cite
|
Sign up to set email alerts
|

Fast-food intake and perceived and objective measures of the local fast-food environment in adolescents

Abstract: Objective: We examined associations between fast-food intake and perceived and objective fast-food outlet exposure. Design: Information from the Health Behaviours in School-aged Children Study was linked to fast-food outlets in seventy-five school neighbourhoods. We used multivariate multilevel logistic regression analyses to examine associations between at least weekly fast-food intake and perceived and objective fast-food outlet measures. Subjects: Data represent 4642 adolescents (aged 11-15 years) in Denmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 81 publications
2
23
2
1
Order By: Relevance
“…We found no evidence of an association between the absolute availability of fast-food restaurants or convenience stores and fast-food or SSB intake, findings which add to the weight of evidence suggesting no effect for the home ( 18 , 32 , 36 ) and school ( 26 , 30 , 32 , 34 – 37 ) neighbourhoods on these dietary outcomes. The null associations found for absolute availability measures in our sample could possibly be explained by the relatively low heterogeneity in the food environment exposures.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…We found no evidence of an association between the absolute availability of fast-food restaurants or convenience stores and fast-food or SSB intake, findings which add to the weight of evidence suggesting no effect for the home ( 18 , 32 , 36 ) and school ( 26 , 30 , 32 , 34 – 37 ) neighbourhoods on these dietary outcomes. The null associations found for absolute availability measures in our sample could possibly be explained by the relatively low heterogeneity in the food environment exposures.…”
Section: Discussioncontrasting
confidence: 51%
“…It also provides evidence specific to a high-density urban context (London, UK) which is of importance since findings from different cities may not be directly comparable because of differences in urban density, form, planning and legislation (54) . We found no evidence of an association between the absolute availability of fast-food restaurants or convenience stores and fast-food or SSB intake, findings which add to the weight of evidence suggesting no effect for the home (18,32,36) and school (26,30,32,(34)(35)(36)(37) neighbourhoods on these dietary outcomes. The null associations found for absolute availability measures in our sample could possibly be explained by the relatively low heterogeneity in the food environment exposures.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Few studies had explored the relationship between the intake of foods classified according to the level of processing and use of different food outlets. 20,21 Since this subject is relatively new, it is reasonable to compare the present results with those of studies that investigated the availability and density of food outlets and the intake of foods, but not necessarily using classifications according to the level of processing.…”
Section: Discussionmentioning
confidence: 90%
“…22 Similar findings were reported among Danish adolescents of the same age, among whom the boys who had greater exposure to fastfood restaurants in the environs of their schools had higher intake of the foods sold at these establishments than did those who were not exposed to these restaurants. 20 Another Canadian study on 810 adolescents aged 11 to 14 found that there was poorer quality of diet, with higher intake of fast foods, among those who lived close to or went to schools close to convenience stores and outlets selling fast foods. 23 Similar results were reported by Laska et al, 24 who found that the sugar-sweetened beverage intake of 349 American adolescents was associated with living close to fast-food restaurants, convenience or grocery stores or any retail facility.…”
Section: Discussionmentioning
confidence: 99%